Formally p-adic Fields - Prestel, Alexander; Roquette, Peter (Lecture notes in mathematics, 1984)
and motivation -- p-valuations -- p-adically closed fields -- The general embedding theorem -- Model theory of p-adically closed fields -- Formally p-adic fields -- Function fields over p-adically closed fields.